2013
DOI: 10.1002/hed.23368
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of transoral laser microsurgery for precancerous lesions and early glottic cancer guided by analysis of voice quality

Abstract: Effect of transoral laser microsurgery on quality of voice depends on the type of cordectomy and the site of the lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 16 publications
6
20
0
1
Order By: Relevance
“…Hence, grading the extent of resection in this study was not reliably feasible by means of distinguishing between type I, type II, or type III resections in both groups, respectively. This is in line with current publications that only distinguish between limited resections (types I‐III) and extended resections (type IV‐V) . Moreover, Greulich et al most recently showed in a meta‐analysis that there is no significant difference in functional voice outcome comparing true European Laryngological Society type I/II resections with type III cordectomies .…”
Section: Discussionsupporting
confidence: 85%
“…Hence, grading the extent of resection in this study was not reliably feasible by means of distinguishing between type I, type II, or type III resections in both groups, respectively. This is in line with current publications that only distinguish between limited resections (types I‐III) and extended resections (type IV‐V) . Moreover, Greulich et al most recently showed in a meta‐analysis that there is no significant difference in functional voice outcome comparing true European Laryngological Society type I/II resections with type III cordectomies .…”
Section: Discussionsupporting
confidence: 85%
“…However, a clear distinction before invasive diagnostic would be essential for therapy planning. On the one hand, as malignant transformation in low dysplasia degrees is rather rare (6,7), unnecessarily augmented excision and the risk of unfavorable scarring could be prevented when presurgical diagnostics would be sufficiently reliable (8). On the other hand, knowing about the malignant nature of a lesion could accelerate the adequate therapy and lead to better functional outcome either by excision or radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The case group included 24 males (80%), and this proportion was similar to that of the control group (n 5 8, 80%). The average number of surgeries that treated the vocal cords was 3.4 (CO 2 : 2.2; KTP: 1.2; range, 1-8) and the average value of the Derkay/Coltrera score at the time of the first surgical intervention was 10.8 (range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. These values were highly correlated with the number of surgeries (r 5 0.72), suggesting that patients with higher preoperative scores tended to require more frequent surgeries.…”
Section: Resultsmentioning
confidence: 99%